Finding the Most Efficient Technology Transfer Route Using Dijkstra Algorithm to Foster Innovation: The Case of Essential Oil Developments in the Research Center for Chemistry at the Indonesian Institute of Sciences - Arief Ameir Rahman Setiawan; Anny Sulaswatty; Agus Haryono (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2016)
Innovation is one of the most critical issues in research institutions which can be performed through certain routes within the technology transfer mechanism. As the demands of research implementation are increasing, a better mechanism should be deployed to foster innovation. This study will investigate the possibilities for technology transfer mechanism improvements by (i) identifying a number of steps required for innovation; (ii) measuring the efficiency of each step; and (iii) exploring the most efficient routes to innovate through the Dijkstra algorithm. Cases of research on essential oils and derivatives in the Research Center for Chemistry (RCC) of the Indonesian Institute of Sciences (LIPI) will be examined as the working example for the study. As a result of this study, a model containing a recommended sequence for the most efficient steps to innovation can be proposed. Using the proposed model, the efficiency rate of the technology transfer mechanism was increased twice, suggesting the possibility of stimulating innovation performance.